2021
DOI: 10.1002/ddr.21811
|View full text |Cite
|
Sign up to set email alerts
|

Neobavaisoflavone protects osteoblasts from dexamethasone‐induced oxidative stress by upregulating the CRNDE‐mediated Nrf2/HO‐1 signaling pathway

Abstract: Neobavaisoflavone (NBIF) is a flavonoid, which has a variety of pharmacological activities. However, the mechanism of NBIF in the treatment of osteoporosis still needs further exploration. The differentiation of osteoblast MC‐3T3‐E1 cells after treatment was observed by Alizarin red staining. Cell counting kit‐8 and flow cytometry were used to detect viability, apoptosis, and reactive oxygen species (ROS) levels of treated MC‐3T3‐E1 cells, respectively. Malondialdehyde (MDA), lactate dehydrogenase (LDH), super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Neobavaisoflavone ( 7 ) was first isolated from the seeds of Psoralea corylifolia , , a plant that is used in traditional Chinese and Indian medicine. Later, it was isolated from root and stem bark of the tree Erythrina sigmoidea in Cameroon. , A wealth of bioactivities have been reported for this natural product, such as antibacterial activity, e.g., against MRSA , or the yeast Zygosaccharomyces parabailii ; the inhibition of DNA polymerase; the stimulation of osteogenesis; the prevention of osteoporosis; or cytotoxicity against human prostate cancer cells . 7-Methoxyneobavaisoflavone ( 9 ) was obtained as a minor component during a phytochemical study on Psoralea corylifolia , and the dimethyl ether 27 was also obtained from neobavaisoflavone ( 7 ) by exhaustive methylation in the course of an isolation study on Erythrina sigmoidea …”
Section: Resultsmentioning
confidence: 99%
“…Neobavaisoflavone ( 7 ) was first isolated from the seeds of Psoralea corylifolia , , a plant that is used in traditional Chinese and Indian medicine. Later, it was isolated from root and stem bark of the tree Erythrina sigmoidea in Cameroon. , A wealth of bioactivities have been reported for this natural product, such as antibacterial activity, e.g., against MRSA , or the yeast Zygosaccharomyces parabailii ; the inhibition of DNA polymerase; the stimulation of osteogenesis; the prevention of osteoporosis; or cytotoxicity against human prostate cancer cells . 7-Methoxyneobavaisoflavone ( 9 ) was obtained as a minor component during a phytochemical study on Psoralea corylifolia , and the dimethyl ether 27 was also obtained from neobavaisoflavone ( 7 ) by exhaustive methylation in the course of an isolation study on Erythrina sigmoidea …”
Section: Resultsmentioning
confidence: 99%
“…MALAT1 overexpression or miR-214 inhibition can ameliorate dexamethasone (DEX)-induced inhibition of osteogenic differentiation of BMSCs ( 57 ). The expression of MALAT1 in pre-osteoblast MC3T3-E1 cells can be down regulated by DEX, which has been demonstrated to inhibit osteoblast proliferation and promote osteoblast apoptosis ( 58 ). More specifically, forced expression of MALAT1 can abrogate DEX-induced viability repression and cell apoptosis by suppressing Ppm1e expression and activating AMPK signaling in OB-6 and hFOB1.19 osteoblast cells ( 59 ).…”
Section: The Roles Of Malat1 In Osteoporosismentioning
confidence: 99%
“…Szliszka et al reported significant inhibition of ROS, reactive nitrogen species (RNS), and the expression of inflammatory cytokines, such as IL-1β, IL-6, IL-12p40, IL-12p70, and TNF-α, in LPS+IFN-γ- or phorbol-12-myristate 13-acetate (PMA)-stimulated RAW264.7 macrophages upon treatment with NBIF. Compounds isolated from Psoralea also stimulate osteogenesis by meditating collagen synthesis to treat bone loss-associated diseases . For example, Xu et al reported that psoralen was shown to work on cartilages, and it promoted cartilaginous gene expressions (e.g., type II collagen, aggrecan, and SOX-9) in rat chondrocytes.…”
Section: Introductionmentioning
confidence: 99%